Synergistic utilization of heavy fraction of tire pyrolysis oil and heavy fuel oil in thermal conversion processes - Poonawala, Taha; Muelas, Álvaro; Ballester, Javier (Jornada de Jóvenes Investigadores del I3A, 2025)
Insights into the characteristic behavior of residual fuel oils needing urgent attention are obtained at conditions representative of relevant thermal conversion processes such as gasification and combustion. To that end, the heavy fraction of tire pyrolysis oil and heavy fuel oil (as representatives of alternative and conventional residual fuels, respectively) are experimentally investigated via isolated droplet method in neat and blended form.